Karakteristik Psikologis Siswa dalam Pembelajaran Matematika ditinjau dari Kecerdasan Intuitif dan Reflektif - Habibullah Habibullah; Gamarina Isti Ratnasari; Puspitarani Puspitarani; Salviana Salviana (KARYA ABDI, 2020)
This research is a descriptive qualitative research using literature review that aims to describe the psychological characteristics of students in learning mathematics on intuitive and reflective intelligence. Intuitive intelligence is a psychological term in the process of cognitive understanding that spontaneously raises and selects known concepts or schemes by understanding knowledge through something concrete, experimental, or intellectually to respond to a stimulus with a high degree of accuracy. While, reflective intelligence is a process of activities carried out actively, persistently, directed and thoughtfully in analyzing, evaluating, motivating, getting deep meaning, and using appropriate learning strategies. Intuitive and reflective intelligence has an important role in learning in school, so it should be developed in the learning process, especially in mathematics so that students can improve their ability to solve problems.